Combustion and emission characteristics of an ultra-lean burn gasoline engine with dimethyl ether auto-ignition. (15th October 2020) - He, Bang-Quan; Xu, Si-Peng; Fu, Xue-Qing; Zhao, Hua
Abstract: To stabilize combustion and shorten combustion duration in ultra-lean homogeneous gasoline-air mixture conditions, the onset of combustion is initiated with the auto-ignition of direct injection dimethyl ether (DME) only through compression in a single-cylinder four-stroke gasoline engine at the lambda of 2.1 at fixed cycle energy. The results show that the heat release processes are dependent on the total DME energy fraction in a cycle in the case of single and split direct injection and the DME fraction in each injection in the case of split direct injection. Increased total DME energy fraction in a cycle decreases the in-cylinder temperature to start low temperature combustion. High DME energy fraction in the second direct injection at a fixed total DME energy fraction in a cycle advances ignition timing, shortens combustion duration and decreases cycle-by-cycle variation of combustion while nitrogen oxides emissions increase although hydrocarbon and carbon monoxide emissions decrease simultaneously. The decrease of the total DME energy fraction in a cycle or that of DME fraction in the second injection at a fixed total DME energy fraction in a cycle is beneficial to the reduction of NOx emissions. Highlights: The combustion of ultra-lean mixture with lambda 2.1 was investigated. Ultra-lean gasoline is burned with single/split direct injection of dimethyl ether. Increased fraction of dimethyl ether in a cycle advances ignition timing. The heat release of gasoline-air mixture is governed by dimethyl ether auto-ignition. Split direct injection of dimethyl ether is benefit for fuel economy improvement.